Interventions for an Artemisinin‐based Malaria Medicine Supply Chain. Issue 9 (15th June 2016) - Kazaz, Burak; Webster, Scott; Yadav, Prashant
Abstract : Artemisinin combination therapy, the most effective malaria treatment today, is manufactured from an agriculturally derived starting material Artemisia annua . Artemisinin, the main ingredient in malaria medicines, is extracted from Artemisia leaves and used in the production of medicine for treating malaria. The artemisinin market has witnessed high volatility in the supply and price of artemisinin extract. A large fraction of malaria medicines for endemic countries in sub‐Saharan Africa is financed by the Global Fund to Fight AIDS, TB, and Malaria and the US President's Malaria Initiative. These agencies together with the World Health Organization, UNITAID, the United Kingdom Department for International Development and the Bill and Melinda Gates Foundation are exploring ways to increase the level of artemisinin production, reduce volatility of artemisinin prices, and improve overall access to malaria medicines for the population. We develop a model of the supply chain, calibrate the model using field data, and investigate the impact of various interventions. Our model shows that initiatives aimed at improving average yield, creating a support‐price for agricultural artemisinin, and a larger and carefully managed supply of semi‐synthetic artemisinin have the greatest potential for improving supply and reducing price volatility of artemisinin‐based malaria medicine.